Impaired contractility of the circular striated urethral sphincter muscle may contribute to stress urinary incontinence in female zucker fatty rats. Issue 6 (29th October 2016) - Lee, Yung‐Chin; Lin, Guiting; Wang, Guifang; Reed‐Maldonado, Amanda; Lu, Zhihua; Wang, Lin; Banie, Lia; Lue, Tom F.
Abstract : Aim: Obesity has been an independent risk factor for female stress urinary incontinence (SUI), the mechanism of this association remains unknown. The aim of this study is to validate the hypothesis that urethral dysfunction is a possible contributor to SUI in obese women. Methods: Ten Zucker Fatty (ZF) (ZUC‐Lepr fa 185) and 10 Zucker Lean (ZL) (ZUC‐Lepr fa 186) female rats at 12‐week‐old were used in this experiment. The urethral sphincter rings were harvested from the bladder neck through to the most proximal 2/3 regions. In the organ bath study, single pulses of electrical field stimulation (EFS) were applied. For the fatiguing stimulation, repeated multi‐pulse EFS with 70 mA were applied at frequency of 5 Hz for 5 min. Caffeine‐containing Krebs' solution was administrated to contract the urethra until the contraction began to reach a plateau for 10 min. We performed immunofluorescence staining of the urethra after the experiment was finished. Results: Compared to ZL controls, ZF rats had significantly impaired muscle contractile activity (MCA) ( P  < 0.05). Also, ZF rats presented early fatiguing of MCA and had a significantly greater percentage of MCA decline from baseline in the fatiguing test (37.7% vs 25.6%, P  < 0.05). The plateau of maximal MCA induced by caffeine in ZF rats was significantly lower than ZL controls (0.22 vs 0.36, P  < 0.05). Conclusions: This novel study showed that obese female rats had significantly impaired contractile properties of striated urethral sphincter, suggesting urethral dysfunction could be an important contributor to SUI in obesity.